The Urban Church Imagined Religion, Race, and Authenticity in the City - Barron, Jessica M.; Williams, Rhys H. (New York University Press, 2017)
Explores the role of race and consumer culture in attracting urban congregants to an evangelical church The Urban Church Imagined illuminates the dynamics surrounding white urban evangelical congregations’ approaches to organizational vitality and diversifying membership. Many evangelical churches are moving to urban, downtown areas to build their congregations and attract younger, millennial members. The urban environment fosters two expectations. First, a deep familiarity and reverence for popular consumer culture, and second, the presence of racial diversity. Church leaders use these ideas when they imagine what a "city church" should look like, but they must balance that with what it actually takes to make this happen.